2018
DOI: 10.1089/jayao.2017.0124
|View full text |Cite
|
Sign up to set email alerts
|

Patient Navigation Preferences for Adolescent and Young Adult Cancer Services by Distance to Treatment Location

Abstract: Purpose: To describe how distance to treatment location influences patient navigation preferences for adolescent and young adult (AYA) cancer patients and survivors. Methods: This study is part of a statewide needs assessment to inform the development of an AYA cancer patient and survivor navigation program. Participants were recruited from outpatient oncology clinics in Utah. Eligible participants had been diagnosed with cancer between ages 15-39 and had completed at least 1 month of treatment. Participants c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
(23 reference statements)
0
10
0
1
Order By: Relevance
“…A study of cancer survivors found that those who lived a great distance from their providers found these services particularly important, especially for logistic questions they were reluctant to ask their cancer providers. 33 Another promising area is the development of telemedicine. This technology has the promise of providing expertise to underserved areas and has had a positive impact in cancer care.…”
Section: Discussionmentioning
confidence: 99%
“…A study of cancer survivors found that those who lived a great distance from their providers found these services particularly important, especially for logistic questions they were reluctant to ask their cancer providers. 33 Another promising area is the development of telemedicine. This technology has the promise of providing expertise to underserved areas and has had a positive impact in cancer care.…”
Section: Discussionmentioning
confidence: 99%
“…That those same individuals had a higher degree of needs met may indicate they had a greater number of initial needs and therefore a higher number of potential needs to meet, with PNs able to address those needs. A recent study supported the use of a PN to help with needs related to general information, finances, psychosocial support and advocated for its use to provide resources remotely to reduce travel burden for non-local/distance survivors [ 30 ]. The physician in charge of follow-up care is a topic of interest in recent literature [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although adolescents and young adults comprise a small percentage of patients with cancer, their medical needs are often unmet [ 15 , 18 ] and specific types of support may be required [ 18 , 19 ]. For example, adolescent and young adult patients may require greater effort to visit the farther and more specialized hospital [ 20 , 21 ]. Younger patients have a larger social role and are thus likely to view outpatient hospital visits as burdensome, which would explain their interest in a weekend chemotherapy option.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports in other countries found that the effort needed to visit the hospital, such as the distance that had to be traveled, affected the prognosis. In Japan, the burden of visiting the hospital may be less than in other countries because of free access to the hospital and the relative ease of travel to local hospitals [ 21 , 30 ].…”
Section: Discussionmentioning
confidence: 99%